If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9X + -2X + -3 = 5X + 2 Reorder the terms: -3 + 9X + -2X = 5X + 2 Combine like terms: 9X + -2X = 7X -3 + 7X = 5X + 2 Reorder the terms: -3 + 7X = 2 + 5X Solving -3 + 7X = 2 + 5X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-5X' to each side of the equation. -3 + 7X + -5X = 2 + 5X + -5X Combine like terms: 7X + -5X = 2X -3 + 2X = 2 + 5X + -5X Combine like terms: 5X + -5X = 0 -3 + 2X = 2 + 0 -3 + 2X = 2 Add '3' to each side of the equation. -3 + 3 + 2X = 2 + 3 Combine like terms: -3 + 3 = 0 0 + 2X = 2 + 3 2X = 2 + 3 Combine like terms: 2 + 3 = 5 2X = 5 Divide each side by '2'. X = 2.5 Simplifying X = 2.5
| 115=5x+15 | | 2ln(x)=ln(7x) | | 8w-4=20 | | -5x-2x+3=0 | | 4x-(12)=60 | | 46=(c+11) | | 43.52=9g+3.56 | | 2ln(x)=ln(7) | | .3(k-2)=.6 | | 1.84g-4=0.60 | | 2(X+5)=2(X-2) | | 3x+8-6x=23 | | -5(x+1)-x-8=-6(x+4)+11 | | 2-5g=3-5 | | 63=3(h-71) | | 30=3n+6 | | 4lnx-7lnx=1 | | 11+3n=20 | | 45c+10b= | | 5x-67=20+8x | | 4lnx+7lnx=1 | | 25p^2-49=0 | | 15t-t= | | -4(-6-3x)=108 | | -204=6(-2+4x) | | (X+50)+(x+60)=90 | | 1.5x=-2y+11 | | (33/4-2/5)+5/8=x | | 0.06g= | | 2.9=7.7-0.6 | | 54=9(y+3) | | 9-5x=2x+4 |